ASIMETRIC PANTOGRAPH MECHANISM STATIC ANALYSIS BY FINITE ELEMENT METHOD - Miklos, Cristina Carmen; Alic, Carmen Inge; Miklos, Imre Zsolt (Acta Technica Corvininesis, 2018)
The paper deals with the static analysis of the asymmetric pantograph mechanism used in the railway electric traction. In order to model the asymmetric pantograph mechanism subject study through the finite element analysis, was used Autodesk Inventor Professional program, a software package that is part of the Computer Aided Design (CAD) family, enables 3D product modeling and assembly of parts, thus representing an integrated and intelligent solution for 2D/3D design dedicated to mechanical and electromechanical engineers. 3D modeling in Autodesk Inventor of the pantograph mechanism was accomplished using the principles of parameterized modeling and adaptability for Stable Part (Part) and 3D constraints: insertion, overlap, angular constraint, insertion (Insert, Mate, Angular, and Flush). After assembly of the component elements and after the introduction of 3D constraints, the pantograph mechanism kinematic verification was performed by simulating the movement. The conclusions and results obtained are useful in the design and operation of these types of mechanisms from the railway electric traction.